A qualitative inquiry into dietary adherence among adults with type 2 diabetes mellitus in India - Alee, Imran; Ayub, Zahid; Ahmad, Naveed (Journal of Community Nursing and Primary Care, 2025)
Background: Dietary adherence is a fundamental component of effective management of type 2 diabetes mellitus (T2DM). However, maintaining dietary compliance remains challenging in culturally diverse and food-centered societies such as India, where traditional dietary practices, social expectations, and family dynamics significantly influence eating behaviors. Objective: This study aimed to explore the lived experiences of adults with type 2 diabetes mellitus in India regarding adherence to dietary recommendations, with particular attention to sociocultural, behavioral, and emotional factors influencing dietary practices. Methods: A qualitative case study design with a positivist approach was employed. Fourteen adults diagnosed with T2DM were recruited through snowball sampling from three Primary Health Centers in India. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis. Strategies to ensure trustworthiness included member checking, audit trails, and data triangulation. Results: Three major themes emerged from the analysis: cultural negotiation of food choices, internalizing health literacy and self-regulation, and family roles and emotional anchors. Participants described challenges in balancing traditional dietary practices with medical recommendations, particularly during social and religious events. Individuals who were able to translate dietary knowledge into daily routines demonstrated stronger adherence behaviors. Family members played an influential role by providing emotional encouragement, assisting with meal preparation, and motivating individuals to maintain dietary discipline. Conclusion: Dietary adherence among adults with T2DM in India is shaped by complex interactions between cultural traditions, health literacy, and family dynamics. Interventions aimed at improving dietary adherence should incorporate culturally sensitive strategies and family-inclusive educational programs to support sustainable self-management.